Lecturer Guidance in Forming Student Character at the Aceh Tamiang Islamic High School - Dinda Rizky Amalia (Tinta Emas Publisher, 2023)
This devotional article aims to describe the guidance of lecturers in shaping the character of students at the Aceh Tamiang Islamic high school. The purpose of this service is as a form of education and information to readers that Islamic tertiary institutions have the task of forming the moral, mental and spiritual character of students based on Islamic religious guidance. The type of writing for this article is a qualitative service that seeks to describe and describe a portrait of the sincere and sincere dedication of lecturers that has been carried out at the Aceh Tamiang Islamic High School and then described in a structured manner by following the applicable rules of writing scientific papers. From the results of the dedication that has been carried out, it was found that: First, the Aceh Tamiang Islamic high school plays an important role by optimizing the campus as the epicenter of character building. Second, the Aceh Tamiang Islamic high school as a center for the establishment of religious moderation in the midst of societal pluralism. Third, the lecturer at the Aceh Tamiang Islamic High School is committed to being the front guard in protecting the nation's religion and morals. Fourth, the Aceh Tamiang Islamic High School makes lecturers not only as educators for students to improve intellectually but also as agents for forming the moral and spiritual character of students.